2018
DOI: 10.1080/20786190.2018.1432138
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the reasons women give for choosing legal termination of pregnancy at Soshanguve Community Health Centre, Pretoria, South Africa

Abstract: Background: Termination of pregnancy (TOP) is one of the most commonly performed gynaecological procedures in the world and was legalised in South Africa in 1996 with the passing of the Choice on Termination of Pregnancy Act, 1996 (Act No. 29 of 1996. Utilisation of the TOP service increased significantly after the promulgation of the Act, to the extent that 7% of pregnant women in South Africa chose to terminate their pregnancies legally in 2012. Worldwide, women most commonly state their reasons for choosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Although the current study did not fully investigate the reasons for unsatisfactory contraceptive practice, other researchers consider that women's lack of economic empowerment, that is, financial stability, makes it difficult for them to negotiate condom or contraceptive use with a reluctant male partner. 17,18 This may result in an unwanted, unplanned pregnancy, and a vicious cycle of repeat TOP, which was found to be higher in South Africa than in developed countries. 4 Some women may go to the extent of keeping their contraceptive use a secret from their male partners who are opposed to contraceptive use in order to control their fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Although the current study did not fully investigate the reasons for unsatisfactory contraceptive practice, other researchers consider that women's lack of economic empowerment, that is, financial stability, makes it difficult for them to negotiate condom or contraceptive use with a reluctant male partner. 17,18 This may result in an unwanted, unplanned pregnancy, and a vicious cycle of repeat TOP, which was found to be higher in South Africa than in developed countries. 4 Some women may go to the extent of keeping their contraceptive use a secret from their male partners who are opposed to contraceptive use in order to control their fertility.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Since the inception of the Act, up to 7% of pregnant women have sought legal ToP in SA. [3] First-trimester terminations are performed as outpatient procedures by trained midwives. Adequate counselling is given, and women are offered the choice of medical or surgical ToP.…”
mentioning
confidence: 99%
“…[2] International data suggest that women decide to have ToP because of a desire to stop or postpone childbearing. [3] Local data indicate that women in the SA setting often have numerous reasons for ToP, such as financial difficulties, formal education not completed, contraceptive failure, wrong timing, and reasons relating to the family or partner. [3] A study in Hammanskraal found that women presenting for ToP were likely to be young, unemployed, poorly educated, in a conflictual relationship with their partner, and dependent on their parents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars who include Bloomer, Pierson, and Claudio (2020) concur with each other that unplanned pregnancy can be a cause of emotional stress, and feelings of guilt, grief, anguish, emptiness, shame, doubt, and anxiety, both before and after abortion. Steyn and Ndimande (2018) argue that poor knowledge of contraception, poor contraceptive practices and contraceptive failure are mentioned as a cause for unplanned pregnancy, and they have a direct impact on abortion.…”
Section: Abortion Decision Makingmentioning
confidence: 99%